Cross-Linking Cellular Prion Protein Induces Neuronal Type 2-Like Hypersensitivity - Adhikari, Utpal Kumar; Sakiz, Elif; Zhou, Xian; Habiba, Umma; Kumar, Sachin; Mikhael, Meena; Senesi, Matteo; Guang Li, Chun; Guillemin, Gilles J.; Ooi, Lezanne; David, Monique Antoinette; Collins, Steven; et al. (Frontiers in Immunology, 2021)
Background Previous reports identified proteins associated with ‘apoptosis’ following cross-linking PrPC with motif-specific anti-PrP antibodies in vivo and in vitro. The molecular mechanisms underlying this IgG-mediated neurotoxicity and the role of the activated proteins in the apoptotic pathways leading to neuronal death has not been properly defined. Previous reports implicated a number of proteins, including apolipoprotein E, cytoplasmic phospholipase A2, prostaglandin and calpain with anti-PrP antibody-mediated ‘apoptosis’, however, these proteins are also known to play an important role in allergy. In this study, we investigated whether cross-linking PrPC with anti-PrP antibodies stimulates a neuronal allergenic response. Methods Initially, we predicted the allergenicity of the epitope sequences associated with ‘neurotoxic’ anti-PrP antibodies using allergenicity prediction servers. We then investigated whether anti-PrP antibody treatment of mouse primary neurons (MPN), neuroblastoma cells (N2a) and microglia (N11) cell lines lead to a neuronal allergenic response. Results In-Silico studies showed that both tail- and globular-epitopes were allergenic. Specifically, binding regions that contain epitopes for previously reported ‘neurotoxic’ antibodies such as ICSM18 (146-159), ICSM35 (91-110), POM 1 (138-147) and POM 3 (95-100) lead to activation of allergenic related proteins. Following direct application of anti-PrPC antibodies on N2a cells, we identified 4 neuronal allergenic-related proteins when compared with untreated cells. Furthermore, we identified 8 neuronal allergenic-related proteins following treatment of N11 cells with anti-PrPC antibodies prior to co-culture with N2a cells when compared with untreated cells. Antibody treatment of MPN or MPN co-cultured with antibody-treated N11 led to identifying 10 and 7 allergenic-related proteins when compared with untreated cells. However, comparison with 3F4 antibody treatment revealed 5 and 4 allergenic-related proteins respectively. Of importance, we showed that the allergenic effects triggered by the anti-PrP antibodies were more potent when antibody-treated microglia were co-cultured with the neuroblastoma cell line. Finally, co-culture of N2a or MPN with N11-treated with anti-PrP antibodies resulted in significant accumulation of NO and IL6 but not TNF-α in the cell culture media supernatant. Conclusions This study showed for the first time that anti-PrP antibody binding to PrPC triggers a neuronal hypersensitivity response and highlights the important role of microglia in triggering an IgG-mediated neuronal hypersensitivity response. Moreover, this study provides an important impetus for including allergenic assessment of therapeutic antibodies for neurodegenerative disorders to derive safe and targeted biotherapeutics.